Made in Cologne : Künstler aus Köln in der DuMont Kunsthalle - Honnef, Klaus; DuMont Kunsthalle, Köln (Köln : DuMont Buchverlag, 1988)
Adamski, Hans-Peter ; Blume, Anna ; Blume, Bernhard Johannes ; Bömmels, Peter ; Buthe, Michael ; Dahn, Walter ; Dokoupil, Jiri Georg ; Genzken, Isa ; Herold, Georg ; Höckelmann, Antonius ; Ikemura, Leiko ; Kippenberger, Martin ; Klauke, Jürgen ; Lüpertz, Markus ; Marx, Karl ; Mields, Rune ; Odenbach, Marcel ; Ortwed, Kirsten ; Paeffgen, C.O. ; Penck, A.R. ; Polke, Sigmar ; Rosenbach, Ulrike ; Schultze, Bernard ; Schulze, Andreas ; Szczesny, Stefan ; Trockel, Rosemarie
Made in Cologne : Künstler aus Köln in der DuMont Kunsthalle, 10. September - 16. November 1988
boek
Keywords: Duitsland; Köln